A new species of Helgreelia Gaimari (Diptera: Odiniidae) from Brazil, with a key to the Neotropical species of Odiniidae - Da Silva Carvalho Filho, Fernando; Esposito, Maria Cristina; de Cássia Oliveira Dos Santos, Rita (Zootaxa, 2009)
The genus Helgreelia Gaimari was previously known only from two species described from Costa Rica. Helgreelia gaimarii n. sp. is described from Brazil based on male and female specimens collected in the Amazon Basin with butterfly traps. A key to the described Neotropical species of Odiniidae is provided.